Elements of physical hydrology - Hornberger, George M. | Raffensperger, Jeffrey P. | Wiberg, Patricia L. (Estados Unidos | ESTADOS UNIDOS The Johns Hopkins University Press / Marylan, 1998)
Contents: The science of hydrology; catchment hydrology: Land-atmosphere interactions; The basic for analysis in physical hydrology; Principles of fluid dynamics open channel hydraulics
Sin Especificar
Keywords: Hidrología